A critical analysis of Lean approach structuring in hospitals. Issue 3 (2014) - Niccolo Curatolo; Samir Lamouri; Jean‐Charles Huet; André Rieutord
<x xml:space="preserve"> Abstract </x> Purpose – As reimbursements fall and costs for services climb, organizations are forced to follow the painful motto of doing more with less. A solution could be the adaptation of industrial business process improvement (BPI) methods such as Lean to the hospital setting (HS). The purpose of this paper is to analyze if Lean approaches related in the literature provide sufficient methodological support for other practitioners to reproduce the reported results. Design/methodology/approach – The authors analyzed the published Lean literature in the HS using a methodological maturity‐level framework and what the authors defined as the 11 characteristic activities of BPI. Findings – The literature analysis reveals that a Lean approach with a high‐methodological maturity level that includes the 11 characteristic activities of BPI has never been reported. Considering this, the paper suggests a meta model for a high‐methodological maturity‐level Lean method based on the characteristic activities of BPI. Originality/value – This is the first study on the Lean approach in the HS that evidences the absence of a robust Lean methodology in the literature. For Lean to be adopted and implemented by hospital practitioners a structured robust method should be provided.